Mercury release from municipal solid waste in the thermal treatment process. (1st December 2022) - Dziok, Tadeusz; Bury, Marcelina; Burmistrz, Piotr
Highlights: Mercury can be easily released from the municipal solid waste by thermal treatment. Different types of waste are characterized by different rates of mercury release. Individual temperature selection for each waste type brings significant benefits. There is a very high potential for producing a low mercury fuel from textiles. Abstract: The use of municipal solid waste for energy generation is becoming more and more important. Sewage sludge from municipal wastewater treatment plants and used car tires constitutes another important group of waste generated by the municipal sector. These types of waste can be utilized through incineration, pyrolysis, and gasification processes. An important issue in their utilization is the release of mercury. Mercury can be emitted into the environment as well as distributed into process products. It is of great importance to determine the behavior of mercury in the thermal treatment process of waste. No detailed studies have been conducted so far. In the paper, selected types of waste generated by the municipal sector were subjected to the pyrolysis process: paper waste, cardboard, plastic, plastic film, textiles, sewage sludge, used car tires as well as an alternative fuel derived from municipal solid waste. The experiments were conducted on a laboratory scale within the temperature range of 150–450 °C. The influence of temperature, residence time, and purge gas flow rate on the release of mercury from the waste was defined. The activation energy for the mercury release process was also determined. The particular types of waste were characterized by different rates of mercury release during thermal treatment. Mercury was most easily released from the textile sample and the release from the plastic sample progressed with utmost difficulty. Research indicates that there is a significant potential for producing low-mercury alternative fuel from waste through thermal treatment.